The Prevention and Control Initiatives for better health of the Medical Technology Students - Rodriguez, Joel (Silliman Journal, 2022)
This article describes the involvement of the Medical Technology students as volunteers in the service-learning program which pursued the prevention and control of intestinal parasitic infection and dengue fever in the community. They conducted stool examination, de-worming, blood typing, and health education among the community residents. Their journals revealed that they were glad for the opportunity to practice their skills and extend their services without much thought of academic reward. What counted more to them was that the program provided them the avenue to practice, improve their skills, and make them aware of the value of cooperation and service above self. They likewise expressed the need to improve the dissemination of the health services available to them to encourage more residents to participate in the health project of the department.